AN APROXIMATE CUT FOR A CLASS OF PROBLEMS OF ENTIRE QUADRATIC PROGRAMATION - Montoro Alegre, Edinson Raúl (2010)
In this work is presented an algorithm that solve a class of integer quadratic program problems. The algorithm solves a secuence of at most  problems of minimum cut over a graph with n + 2 vertex where n is the number of variables in the problem.